EFEKTIVITAS EKSTRAK ETANOL DAUN BELUNTAS PLUCHEA INDICA (L.) LESS TERHADAP BAKTERI SALIVA SECARA IN VITRO - Annisa Fairus Syafira; Masyhudi Masyhudi; Sinar Yani (ODONTO : Dental Journal, 2019)
Background: Pluchea indica (L.) Less leaf contains antibacteria substances that can inhibit the growth of bacteria that cause dental and oral diseases. Previous research shows that Pluchea indica (L.) Less leaf extract can inhibit the growth of Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa bacteria. This research aimed to find out effectiveness of Pluchea indica (L.) Less leaves to decrease in the number of salivary bacteria colony.Method: This research used a sample of saliva obtained from a person who has dental caries. The saliva had been treated with Pluchea indica (L.) Less leaves ethanol extract with concentration 2,5%, 3,5%, 4,5%, 5,5%, and 6,5%. Bacterial colonies were calculated using a colony counter and no identification was performed.Result: The mean of bacteria colony number in Plate Count Agar media without Pluchea indica (L.) Less leaves ethanol extract is 142,67. After being given Pluchea indica (L.) Less leaves ethanol extract with concentration of 2,5%, 3,5%, and 4,5%, the mean of bacteria colony number sequentially are 15,67, 10,67, 4, and at a concentration of 5.5% and 6.5% no more bacterial colonies were found.Conclusion: Pluchea indica (L.) Less leaves ethanol extract effective to inhibit and eliminate oral bacteria.